Constipation during Entecavir treatment in Chronic Hepatitis B patients: Two Cases Reports - Meng-Lan Wang; Dong-Mei Zhang; En-Qiang Chen (Archives of Hepatitis Research - Peertechz Publications, 2017)
Entecavir (ETV) is an oral nucleoside analog inhibitor of hepatitis B virus (HBV) DNA polymerase, which is widely used in patients with chronic hepatitis B (CHB). Despite the excellent safety data of this agent, the adverse events of headache, diarrhea, nausea and vomiting are recorded in the drug instruction of ETV. Here we report two CHB patients with ETV-associated constipation in whom symptom fully disappeared following ETV withdrawal.